Diagnosis and treatment in chronic pancreatitis: an international survey and case vignette study. Issue 11 (November 2017) - ,; Moody, Frank G.; Bertrand, Claude; Johnson, Colin; van Lander, Aude; Carter, Ross; Conneely, John B.; Berrevoet, Frederik; Sousa Silva, Donzília; Li, Zong-Fang; Lévy, Philippe; Oppong, Kofi; et al.
Abstract: Background: The aim of the study was to evaluate the current opinion and clinical decision-making process of international pancreatologists, and to systematically identify key study questions regarding the diagnosis and treatment of chronic pancreatitis (CP) for future research. Methods: An online survey, including questions regarding the diagnosis and treatment of CP and several controversial clinical case vignettes, was send by e-mail to members of various international pancreatic associations: IHPBA, APA, EPC, ESGE and DPSG. Results: A total of 288 pancreatologists, 56% surgeons and 44% gastroenterologists, from at least 47 countries, participated in the survey. About half (48%) of the specialists used a classification tool for the diagnosis of CP, including the Mayo Clinic (28%), Mannheim (25%), or Büchler (25%) tools. Overall, CT was the preferred imaging modality for evaluation of an enlarged pancreatic head (59%), pseudocyst (55%), calcifications (75%), and peripancreatic fat infiltration (68%). MRI was preferred for assessment of main pancreatic duct (MPD) abnormalities (60%). Total pancreatectomy with auto-islet transplantation was the preferred treatment in patients with parenchymal calcifications without MPD abnormalities and in patients with refractory pain despite maximal medical, endoscopic, and surgical treatment. In patients with an enlarged pancreatic head, 58% preferred initial surgery (PPPD) versus 42% initial endoscopy. In patients with a dilated MPD and intraductal stones 56% preferred initial endoscopic ± ESWL treatment and 29% preferred initial surgical treatment. Conclusion: Worldwide, clinical decision-making in CP is largely based on local expertise, beliefs and disbeliefs. Further development of evidence-based guidelines based on well designed (randomized) studies is strongly encouraged.